Community structure of algae epiphytic in different leaf litter of mangroves - Riche Hariyati; Sri Widodo Agung Suedy; Rully Rahadian (NICHE Journal of Tropical Biology, 2018)
Mangrove is a plant that has the morphological and physiological adaptations to habitats which influenced by a tide. This plant can grow and develop in an environment of high salinity and its soil conditions are less stable and aerobic. Litter mangrove is the main source for the availability of detritus and is the largest component constituent of a food web in a mangrove ecosystem environment. Algae epiphytic microalgae is a group that lives attached to the plant, including the mangrove litter. The study aims to assess the abundance and diversity of epiphytic algae on different types of mangrove leaf litter. The observed mangroves leaf litter were Avicennia alba, Sonneratia sp. and Rhizophora sp. Epiphytic algae were brushed on mangrove leaf litter covering an area of 6.25 cm2 and diluted with distilled water. Samples were observed under a microscope with a magnification of 400 x. Water quality parameters were measured in situ and the organic ingredients, total N and P were analyzed. The results showed that epiphytic algae on each type of mangrove leaf litter were not different. Rhizophora sp is the most abundant and the richest species compared with other types of litter that are equal to 622 individuals / cm2 and 26 species of epiphytic algae. While the abundance of Avicennia alba and Sonneratia sp were 459 ind/cm2 and 321 ind /cm2, in the coastal mangrove areas of Morodemak was found 28 species of epiphytic algae. The common epiphytic algae species found in all types of mangrove litter were Cymbella sp., Coscinodiscus sp., and Synedra ulna. In general, the group of Bacillariophyta (diatoms) is the dominant species in some mangrove leaf.